The Role of Physical Activity in the Prevention and Management of Mental Health Disorders: A Review - Romaniuk, Sergiusz; Jurczuk, Aleksandra; Bałdyga, Paulina; Marciniak, Kinga; Wilczyńska, Aleksandra (Journal of Education, Health and Sport, 2025)
Introduction and Purpose: Mental health disorders such as depression, anxiety, and stress-related conditions are major contributors to global disability. Growing evidence indicates that physical activity is an effective non-pharmacological strategy for preventing and managing these conditions. This review aims to summarize current knowledge on the impact of physical activity on mental health and the mechanisms through which it exerts its effects. Material and Method: A narrative review was conducted using PubMed, Scopus, and Google Scholar to identify studies from 2010-2025 examining physical activity and mental health outcomes in adults. Priority was given to randomized trials, systematic reviews, and meta-analyses exploring exercise-based interventions and their psychological or physiological effects. Results: The analyzed literature shows that regular physical activity - particularly aerobic and moderate-intensity exercise - supports mood regulation, enhances cognitive functioning, and increases resilience to stress. Reported mechanisms include neurobiological changes such as improved neurotransmitter balance, reduced inflammation, and enhanced neuroplasticity, alongside psychological benefits such as increased self-efficacy and reduced rumination. Structured exercise programs also demonstrate efficacy as adjuncts to psychotherapy and pharmacotherapy. Conclusions: Physical activity represents a valuable and evidence-based component of mental health promotion and treatment. Incorporating tailored exercise interventions into prevention strategies and clinical care may significantly improve psychological well-being and reduce the burden of mental health disorders